Response inhibition or salience detection in the right ventrolateral prefrontal cortex? - Walther, Stephan; Friederich, Hans-Christoph; Stippich, Christoph; Weisbrod, Matthias; Kaiser, Stefan (Neuroreport, 2011)
This study addresses the question of whether frontal activation in response-inhibition tasks is specifically associated with the suppression of a motor response. An alternative model suggests a role in the detection of behaviorally relevant or salient events. For this purpose, we used functional MRI with an auditory go/no-go paradigm. This paradigm allowed the disentangling of inhibition-related from salience-related effects, which were associated with different frontal regions. Importantly, the right ventrolateral prefrontal cortex consistently showed sensitivity for salience but not for inhibition requirements. This reflects a more general salience-detection mechanism, which is not specific for response-inhibition tasks.
Gesehen am 07.11.2022